2013
DOI: 10.1007/s40262-013-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–Toxicity Relationship of Sorafenib in Japanese Patients with Renal Cell Carcinoma and Hepatocellular Carcinoma

Abstract: The results of this study suggest that the safety and pharmacokinetic profiles of sorafenib differ between Japanese cancer patients with RCC and HCC. Furthermore, the serum sorafenib concentration could be used as a guide to avoiding the development of severe HFSR while allowing prediction of the incidence of grade ≥2 hypertension in patients with RCC and HCC, and may potentially be related to the clinical efficacy of sorafenib for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 39 publications
8
52
2
Order By: Relevance
“…Different PK/PD studies have documented the relationship between severe drug-induced toxicities and plasma concentration of tyrosine kinase inhibitors such as sunitinib, erlotinib, sorafenib [7,8,[21][22][23][24]. The present study is the first to show that an increased concentration of vemurafenib is associated with an increased risk of grade≥2 skin rash in the first 3 months of treatment.…”
Section: Discussionsupporting
confidence: 48%
“…Different PK/PD studies have documented the relationship between severe drug-induced toxicities and plasma concentration of tyrosine kinase inhibitors such as sunitinib, erlotinib, sorafenib [7,8,[21][22][23][24]. The present study is the first to show that an increased concentration of vemurafenib is associated with an increased risk of grade≥2 skin rash in the first 3 months of treatment.…”
Section: Discussionsupporting
confidence: 48%
“…Severe HFSR (grade ≥2) has been reported to be related to plasma drug concentration, cumulative drug area under the curve, and maintenance dose [21][22][23][24]. In the present study, no statistical difference was observed between non-HFSR and HFSR groups with regard to the initial doses patients received (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…Sorafenib steady‐state concentrations were found to be higher in patients with Grade ≥2 hand‐foot syndrome and hypertension than in those not experiencing these AEs ( P = 0.0045 and 0.0453, respectively). Optimal cutoffs were 5.78 mg/L for hand‐foot syndrome and 4.78 mg/L for hypertension 69. In a small cohort of 25 hepatocellular carcinoma patients, the AUC‐ratio of sorafenib and its metabolites resulted in even better prediction of toxicity ( P = 0.002) 70.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 99%